Traveling in networks with blinking nodes - Carrigan, Braxton; Hammer, James (Theory and Applications of Graphs, 2018)
0 citations (Crossref) [2023-10-31]
Keywords: dept.mat; peer-reviewed

A regional Kronecker product and multiple-pair latin squares - Carrigan, Braxton; Hammer, James; Lorch, John (Discrete Mathematics, 2020)
We introduce a variant of the Kronecker product, called the regional Kronecker product, that can be used to build new, larger multiple-pair latin squares from existing multiple-pair latin squares. We present applications to the existence and orthogonality of multiple-pair latin squares. © 2019 Elsevier B.V.
2 citations (Crossref) [2023-10-31] tex.ids: carriganRegionalKroneckerProduct2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85076148310 type: Article
Keywords: Factor pair latin squares; Multiple pair latin squares; Sudoku pair latin squares; dept.mat; peer-reviewed

Constructing (3, B)-sudoku pair latin squares - Carrigan, Braxton; Diaz, David; Hammer, James; Lorch, John (Australasian Journal of Combinatorics, 2022)
An (a, b)-Sudoku pair Latin square is a Latin square that is simult-aneously an (a, b)-Sudoku Latin square and a (b, a)-Sudoku Latin square. While (a, b)-Sudoku Latin squares are known to exist for any positive integers a and b, the pairs a, b for which an (a, b)-Sudoku pair Latin square exists are largely unknown. In this article we establish the existence of (a, b)-Sudoku pair Latin squares for an infinite collection of pairs (a, b). Our results show that a (3, b)-Sudoku pair Latin square can be constructed for any positive integer b. ©The author(s).
Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85121634938
Keywords: dept.mat; peer-reviewed; ⛔ No DOI found

List colorings count rokudoku-pair squares - Carrigan, Braxton; Hammer, James; Lorch, John; Lorch, Robert; Owens, Caitlin (Bulletin of the Institute of Combinatorics and its Applications, 2021)
A rokudoku-pair square is an order-6 sudoku Latin square for both 2 x 3 and 3 x 2 tiling regions simultaneously. We count the distinct rokudoku-pair squares as well as orbits under the action of a suitable group. Our arguments employ group actions and list colorings of graphs. As an application we determine which rokudoku-pair squares are based on groups. © 2021. All Rights Reserved.
Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85109428650
Keywords: dept.mat; peer-reviewed; ⛔ No DOI found